Melatonin protects against Epirubicin-induced ovarian damage - Naiqiang WANG; Hua LI; Yunqing ZHU; Na LI; Zi-Jiang CHEN; Cong ZHANG (The Society for Reproduction and Development, 2019)
One major side effect of chemotherapy that young women with cancer suffer from is ovarian damage. Therefore, it is necessary to study the pathogenesis of chemotherapeutic drugs in order to develop pharmaceutical agents to preserve fertility. Epirubicin is one of the commonly used chemotherapy drugs for breast cancer patients. This research explored the side effects of epirubicin in mice. We found that epirubicin significantly reduced the body weight, the weight of the ovaries and uteri, and the pups' number, while melatonin, which is extremely resistant to oxidation, significantly reduced these damages. Moreover, co-treatment with melatonin prevented epirubicin-induced decrease in E2 and progesterone, and the loss of follicles. Mechanism study showed that melatonin significantly reduced the levels of proapoptotic genes p53, Caspase3, and Caspase9 while it upregulated antiapoptotic factors Bcl-2 and Bcl2l1, and antioxidant genes superoxide dismutase 1 and catalase compared with the epirubicin group. In addition, melatonin markedly reduced reactive oxygen species (ROS) and the transcription of Caspase12 and Chop, which is vital in endoplasmic reticulum stress (ERS)-mediated apoptosis. These results indicate melatonin protects against epirubicin-induced ovarian damage by reducing ROS-induced ERS. Therefore, melatonin has a therapeutic potential for the protection of ovarian function and preservation of fertility during chemotherapy.